Towards a transformative and holistic continuing self-directed learning theory - Du Toit-Brits, C. (South African Journal of Higher Education, 2020)
This article encompasses the theoretical motivation for a proposed self-directed learning (SDL) theory by means of a literature review of SDL and the presentation of the anticipated theory/model. Over the previous decades, SDL has been an active area of inquiry in adult education and learning. There were several efforts to construct models/theories for helping elucidate the notion and foundations of SDL. Models are fluid because of subsequent research and enhanced understanding and in principle, a model should develop over time grounded on ongoing research. Therefore, for this paper‘s purpose the author will present another conceptual model and description/definition of SDL to bring to the fore the intricacy of SDL, based on my enhanced understanding. This model proposes yet another understanding of SDL. Key words for index purposes: control, learning, learners, learning environment, teachers, self-directed learning, self-directedness.